Duncan–Chang damage model of granite residual soil under acidic conditions - Liang, Di; Dang, Fang; Wang, Ya; Li, Yang; Guo, Hong (Frontiers in Earth Science, 2025)
To study the mechanical properties of granite residual soil under acid leaching conditions, triaxial consolidated undrained shear tests were conducted on granite residual soil collected from Chenggu County, Hanzhong City. In the experiments, environments with different acidities were simulated, and the shear stress–strain relationship of the soil under different acidities was determined by adjusting the molar concentration of the acid solution. The results indicated that as the molar concentration of acid increased, the shear stress of granite residual soil decreased significantly, especially under high confining pressure conditions, where the attenuation effect of acid on shear stress is more significant. These findings indicated that the acid sensitivity of the soil increased in acidic environments, and the degree of consolidation significantly affected acid sensitivity. Based on experimental data, a Duncan–Chang constitutive model considering acid-induced damage was established, and the applicability of the model was confirmed through parameter analysis. The adjustment of model parameters can reflect the effect of acid damage on the internal friction angle and cohesion of soil. Additionally, this study revealed a quantitative relationship between acid damage and the molar concentration of H+. The acid damage coefficient can be determined by fitting the curve, providing a basis for predicting the mechanical behavior of soil under different acidic conditions. This study provided a new perspective for understanding the mechanism of damage to granite residual soil during acidification.